International Consumer Behavior in the 21st Century Impact on Marketing Strategy Development - Samli, A. Coskun. (Springer New York : Imprint: Springer, 2013)
Over the past two decades, the face of the world consumer has truly changed. Goods are more available, information about these goods is more open and accessible, and the ability to buy these goods from any corner of the earth has become possible. As a result, international marketing is more important now than ever before. In this book, Josh Samli explores the challenges facing modern international marketers. He explains what it is to have successful communication with the target market: using social media to share consistent information about products and services, communicating directly with culture-driven consumers who already communicate online amongst themselves and with competitors, and mastering people-to-people communication with both privileged and non-privileged consumers. Any company dealing with international marketing must learn how to handle these new challenges in order to survive in the 21st century.